Transgenerational Inheritance of Reproductive and Metabolic Phenotypes in PCOS Rats - Zhang, Hao-Lin; Yi, Ming; Li, Dong; Li, Rong; Zhao, Yue; Qiao, Jie (Frontiers in Endocrinology, 2020)
Androgen exposure of female fetuses could be an important factor in the development of polycystic ovary syndrome (PCOS) in subsequent generations. The present study aimed to investigate the transgenerational effects of PCOS on the growth, reproduction, and metabolism of the first- and second-generation offspring in rats. Female F0 rats received excessive dehydroepiandrosterone (DHEA) exposure to establish PCOS or the same amount of vehicle as controls. These F0 females were crossed with normal males to obtain control (C) and DHEA (D) F1 offspring, whereas F2 offspring were obtained by inter-crossing between F1 rats for 4 groups: (1) C♂-C♀; (2) D♂-C♀; (3) C♂-D♀ and (4) D♂-D♀. Compared with control groups, F1 and F2 offspring with ancestral DHEA exposure showed higher body weight with increasing age. In addition, female F1 and F2 offspring with ancestral DHEA exposure exhibited PCOS-like reproductive and metabolic phenotypes, including disrupted estrous cycles and polycystic ovaries, as well as increased serum levels of testosterone, impaired glucose tolerance and widespread metabolic abnormalities. Male offspring with ancestral DHEA exposure exhibited lower quality of sperms. These findings confirm the negative effects of excessive androgen exposure of female fetuses on subsequent generations.